PENERAPAN PENDEKATAN INTEGRATIF DALAM MENINGKATKAN KEMAMPUAN MEMAHAMI ISI BACAAN PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV MI MIFTAHUL HUDA TUNAH SEMANDING TUBAN TP 2021/2022 - Nur Afiyani (PREMIERE : Journal of Islamic Elementary Education, 2022)
The background of this research is the low ability of students to understand the content of reading in Indonesian subjects in class IV MI Miftahul Huda Tunah students. This study aims to determine how the application of an integrative approach in improving the ability to understand the content of students' reading content, to determine the ability to understand students' reading content, to determine the increase in the ability to understand the content of reading after the application of an integrative approach in class IV MI Miftahul Huda, Tunah District, Tuban Regency on the subject of Language. Indonesia. This research uses classroom action research with quantitative analysis and qualitative analysis of the data collected through observation and tests. The data obtained were analyzed to obtain information about the development of students during the learning process. From the results of research that has been carried out, it is known that the application of an integrative approach in improving the ability to understand students' reading content obtained the following results. The acquisition value of the ability to understand the contents of students' reading before the action was taken was 48.86% in the 0-74% interval in the low category with classical completeness of 15.78%. After taking action in the first cycle, the score increased to 66.81% with classical completeness of 50.01% in the low category. Because it was felt that the results obtained in the first cycle had not reached the desired completeness, the second cycle was carried out with an average acquisition of 76.57% with classical completeness of 86.84% being in the high category. From the results of research that has been carried out by researchers, it can be concluded that the application of an integrative approach can improve students' ability to understand the content of reading.